Indicators of health system coverage and activity in Ireland during the economic crisis 2008-2014 - From 'more with less' to 'less with less'. - BARRY, SARAH; THOMAS, STEPHEN; BURKE, SARA (My University, 2014)
A new Irish government came to power in March 2011 with the most radical proposals for health system reform in the history of the state, including improving access to healthcare, free GP care for all by 2015 and the introduction of Universal Health Insurance after 2016. All this was to be achieved amidst the most severe economic crisis experienced by Ireland since the 1930s. The authors assess how well the system coped with a downsizing of resources by an analysis of coverage and health system activity indicators. These show a health system that managed ‘to do more with less’ from 2008 to 2012. They also demonstrate a system that was ‘doing more with less’ by transferring the cost of care onto people and by significant resource cuts. From 2013, the indicators show a system that has no choice but ‘to do less with less’ with diminishing returns from crude cuts. This is evident in declining numbers with free care, of hospital cases and home care hours, alongside increased wait-times and expensive agency staffing. The results suggest a limited window of benefit from austerity beyond which cuts and rationing prevail which is costly, in both human and financial terms.
PUBLISHED
Keywords: Health system; Coverage; Activity; Rationing; Ireland: Economic crisis; Health reform; Austerity; Cost cutting; Inclusive Society